Ex‐situ catalytic fast pyrolysis of low‐rank coal over HZSM‐5 and modified Mg/HZSM‐5 catalysts. (28th August 2021) - Amin, Muhammad Nadeem; Ahmed, Ashfaq; Li, Yi; Li, Chunshan; Zhang, Suojiang; Ammar, Muhammad; Park, Young‐Kwon
Summary: Catalytic effects in fast pyrolysis of low‐rank coal and coal tar conversion were investigated in a two‐stage fixed‐bed reactor over HZSM‐5 zeolite and Mg/HZSM‐5. Mg/HZSM‐5 caused the lower total tar yield and the higher non‐condensable gas yield but the fraction of light tar (boiling point below 360°C) increased to allow a slightly higher total yield of light tar. It also exhibited good catalytic activity and increased the species of light tar than HZSM‐5 zeolite. The light tar fraction was increased from 45 to 74.6 wt% than without catalyst (66%) at the pyrolysis temperature of 600°C. Ex‐situ catalytic fast pyrolysis over Mg/HZSM‐5 also lowered the contents of element N and S in the resulting coal tars by 29% and 15% respectively. The corresponding increase in the content of element H and molar ratio of H to C of the resulting coal tars was reported as 17% and 13% respectively. The addition of Mg into HZSM‐5 increased the ability of the catalyst for inhibiting coke deposition. Abstract : The Introduction of basic oxide catalyst (MgO) into acidic ZSM‐5 zeolite was investigated to study the catalytic fast pyrolysis of low rank coal at various temperatures. The fraction of light tars produced over the Mg/HZSM‐5 catalyst increased up to 66% compared to noncatalytic study and it promoted the yield of noncondensable gases and reduced Co2 production. A better catalytic activity was shown by Mg/HZSM‐5 by suppressing the tar deposition because of more acidic sites compared to ZSM‐5 zeolite.